Manajemen Prinsip Bandar Udara - Akbar, Muhammad Caesar; Iqbal, M. Yusuf; Agiska, Tiara (MODELING: Jurnal Program Studi PGMI, 2024)
Airport management is very important and plays a very important role in increasing the growth of the aviation sector and the economy, because every time there is movement of aircraft traffic carrying out arrival and departure activities from an airport, both domestic and international. The aim of this research is to find out (1) the role of an airport, (2) how an airport is managed, (3) the difference between commercial airports and airports managed by the Air Force. This research method is a literature study and an exploratory descriptive approach. It can be concluded that: the important role of airports, namely as a node of the air transportation network, a door to economic sustainability, a place for activities to change modes of transportation, opening regional isolation, handling disasters, and infrastructure to strengthen state sovereignty. The private sector needs to be involved in the form of cooperative operations and management contracts with major capital expenditure, which is mostly realized in government-private cooperation in airport management.